The three-step persuasion model on YouTube: A grounded theory study on persuasion in the protein supplements industry - Tripathi, Jayanshi; de Vries, Roelof A. J.; Lemke, Mailin (Frontiers in Artificial Intelligence, 2022)
Persuasion can be defined as an active attempt by a person to change the behavior and attitudes of others. The purposive attempt to influence one's behavior can originate from different areas, and people who are able to do so are often referred to as influencers. Social media platforms such as Instagram or YouTube have become crucial platforms for influencers who generate their income by recommending products and services to their followers, including cosmetics, multimedia articles or clothing. Studies indicate that influencers actively try to persuade the viewer to adopt specific desirable behavior by strategically altering their displayed behavior on social media. Such strategies have mainly been explored in the context of beauty products, where lack of expertise and misinformation might have few negative consequences. Less is known about strategies used in a health-sensitive context, such as nutritional supplements. This research addresses this gap and aims to understand persuasive techniques used by health professionals on YouTube to promote the use of protein supplements. This study is based on an interpretive paradigm using interpretive grounded theory to analyze 60 YouTube videos. We developed a three-step model of persuasion for YouTube videos consisting of the steps: reaching the message, staying on the message, and performing the action that the persuader desires. Our analysis resulted in five core themes that contributed to the persuasiveness of the analyzed YouTube videos. These themes included: Quality, curiosity, engagement, concretization, and genuineness. We conclude the paper with reflections on our model's theoretical and practical implications.